1998
DOI: 10.3319/tao.1998.9.3.301(taicrust)
|View full text |Cite
|
Sign up to set email alerts
|

Onshore/Offshore Wide-Angle Deep Seismic Profiling in Taiwan

Abstract: In summer 1995, in collaboration with the deep multi-channel seismic profiling project around the island of Taiwan, an onshore-offshore wide angle deep seismic profiling experiment was conducted in Taiwan. The re sults are expected to provide the first complete seismic images of the deep crustal structure for a better understanding of the Taiwan orogeny and subduction-collision system. The experiment consists of three profiles, one along each of the central and southern cross-island highways and another on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 12 publications
6
52
1
Order By: Relevance
“…TAICRUST, was carried out in 1995 (e.g., Shih et al, 1998;Yeh et al, 1998;and McIntosh et al, 2005). Although it was a fruitful experiment, owing to the active sources (air guns) mainly from the eastern areas offshore of Taiwan, the depth resolution was limited to above 20-30 km (McIntosh et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TAICRUST, was carried out in 1995 (e.g., Shih et al, 1998;Yeh et al, 1998;and McIntosh et al, 2005). Although it was a fruitful experiment, owing to the active sources (air guns) mainly from the eastern areas offshore of Taiwan, the depth resolution was limited to above 20-30 km (McIntosh et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2) and (2) the arrival times of P-and S-waves generated by earthquakes occurring in the vicinity of Taiwan. Air-gun sources were released by the R/V Maurice Ewing on the southeastern offshore area of Taiwan in September 1995 (e.g., Yeh et al, 1998) and recorded by the CWBSN stations in subarea D. In addition, the air-gun signals recorded by an ocean bottom seismometer (OBS) (Chen and Nakamura, 1998) were also included in the data set for the 3-D inversion. A study of the crustal structure using air-gun and earthquake data in subarea D can provide us with a detailed velocity model from shallow to deeper crust that permits us to study the crustal deformation associated with the transition from subduction to collision.…”
Section: Traveltime Datamentioning
confidence: 99%
“…This fact, together with other geophysical evidence, led Wu et al (1997) to argue that the Taiwan orogeny was the result of lithospheric thickening instead of thin-skinned tectonics. Recent studies on wide-angle deep seismic profiling suggested significant crustal thickening in both the Eurasian plate and the Philippine Sea plate near the suture zone (e.g., Shih et al, 1998;Yeh et al, 1998), which is inconsistent with the thin-skinned model.…”
Section: Tectonic Setting Of Taiwanmentioning
confidence: 93%